Neuroprotective effects of Cassia tora against paraquatinduced neurodegeneration: Relevance for Parkinson’s disease - Sunil K. Ravi (2019)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. The aim of the present study was to determine whether Cassia tora extracts could reverse the oxidative stress-induced neurodegeneration in a Parkinson’s disease in vitro model. The leaves were treated with ethyl acetate (CtEA) or methanol (CtME). The extracts were first analysed by HPLC for their phenolic content and then tested for their neuroprotective effects in human SK-N-SH neuroblastoma cells. Cells were pre-treated with various concentrations of extracts followed by incubation with paraquat (14 μM). Firstly, pre-treatment of SK-N-SH cells with 100 μg/mL of CtEA or CtME significantly reduced the paraquat-induced production of reactive oxygen species. Furthermore, both CtEA and CtME reduced the paraquat-induced apoptosis. Moreover, there was a significant reduction of paraquatinduced DNA damage in SK-N-SH cells pre-treated with CtEA or CtME. Finally, both extracts significantly inhibited paraquat-dependent lipid peroxidation. Altogether, these in vitro data establish C. tora as a possible anti-Parkinson natural remedy.